Composition of the Volatile Oils of Two Anthemis L. Taxa from Turkey - Kilic, Omer; Kocak, Alpaslan; Bagci, Eyup (Verlag Z Naturforsch, 2011)
The essential oils of water-distilled aerial parts of Anthemis pseudocotula and Anthemis cretica subsp. pontica (Asteraceae) were analysed by GC-MS. As a result thirty-five and forty compounds were identified representing 93.1% and 89.0% of the oils, respectively. The main compounds of A. pseudocotula were 1,8-cineole (39.40%), camphor (9.36%), artemisiaketone (5.68%), filifolene (5.15%), and alpha-terpineol (4.69%), whereas beta-caryophyllene (20.26%), azulene (14.98%), spathulenol (6.03%), and germacrene D (5.82%) were the major constituents of A. cretica subsp. pontica.
Keywords: Anthemis; 1,8-Cineole; Caryophyllene